Communication Style as an Antecedent to Reactance, Self-Efficacy, and Restoration of Freedom for Drug- and Alcohol-Involved Women on Probation and Parole. Issue 5 (3rd May 2016) - Smith, Sandi W.; Cornacchione, Jennifer J.; Morash, Merry; Kashy, Deborah; Cobbina, Jennifer
Abstract : This study extends research on psychological reactance theory by examining probation and parole officer (PO) communication style as an antecedent to female offenders' reactance and 2 indicators of subsequent drug and alcohol abuse while serving probation or parole sentences. Structural equation modeling was conducted to test a mediational path model, the results of which demonstrated that perceptions of PO conversational communication style were negatively associated with reactance but positively associated with self-efficacy to avoid drugs and alcohol. Conversely, women who perceived their POs as having a conformity communication style were more likely to report higher levels of reactance and lower self-efficacy to avoid drugs and alcohol. Psychological reactance led to desire to restore freedom, whereas self-efficacy to avoid drugs and alcohol did not. Desire to restore freedom was linked with reports of using drugs and alcohol and violations of parole or probation for using drugs and alcohol. These findings highlight the importance of communication style as an antecedent to reactance and in the relationship between POs and offenders.